Determinants of Job Satisfaction With Employee Performance: Determinant Kepuasan Kerja Terhadap Kinerja Karyawan - Husainah, Nazifah; Maswanto; Haryoto, Cecep (Procedia of Social Sciences and Humanities, 2022)
This research is an associative quantitative study using primary data, with a population of 140 and a sample of 103 people, the determination of the sample using the Slovin formula. The data analysis model used is path analysis using SPSS The results showed the following results: Leadership style has a direct effect on job satisfaction, Human resource development has a direct effect on job satisfaction, Leadership style has a direct effect on employee performance,Human resource development has a direct and indirect effect. Job satisfaction has adirect effect on employee performance (6) Leadership style has an indirect effect on employee performance through job satisfaction, Human resource development has an indirect effect on employee performance through job satisfaction. It can be concluded that there is an indirect effect of leadership style and human resource development on employee performance through job satisfaction, but the direct influence of human resource development on job satisfaction has the greatest influence, while for the direct effect of human resource development on performance is the smallest influence.